Combined therapy in diabetic macular edema - González Cortés, Jesús Hernán; Toledo Negrete, Juan José; Butrón Valdez, K.; Zapata Elizondo, V.; Martínez Gamero, Bertha Olivia; Treviño Cavazos, Ezequiel Enrique; Guerra Leal, Jesús Dante; Mohamed Hamsho, Jesús (UANL. Facultad de Medicina, 2015)
Purpose: To determine the effectiveness of three different combinations for the ‘‘loading phase’’ in the treatment of diabetic macular edema (DME), using bevacizumab (BVZ), triamcinolone (TCL) and subthreshold macular photocoagulation (SMPC). Methods: Experimental, longitudinal, prospective, comparative and blind. Patients were randomly assigned to three treatment branches: Group 1: BVZ + SMPC (12 eyes), Group 2: SMPC + BVZ + TCL (7 eyes), Group 3: BVZ + TCL (11 eyes). Treatment with BVZ and TCL was given every 4 weeks for 3 months, SMPC was applied once at the beginning of treatment. Initial and final measurements of best corrected visual acuity (BCVA), central macular thickness (CMT) and intraocular pressure (IOP) were tested. Results: The improvement in BCVA and the reduction in CMT was statistically superior in group of BVZ + SMPCwhen compared to the other groups. There were no differences in IOP. Conclusions: Combined therapies in the ‘‘loading phase’’are a good option when treating DME. Although the group with BVZ + SMPC obtained the best results, further studies with longer followup and a higher number of participants to establish this combined therapy as the first treatment option are required.